Antiproton stopping in atomic targets - Bailey, J.; Kadyrov, Alisher; Abdurakhmanov, Ilkhom; Fursa, Dmitry; Bray, Igor (American Physical Society, 2015)
© 2015 American Physical Society. ©2015 American Physical Society. Stopping powers of antiprotons in H, He, Ne, Ar, Kr, and Xe targets are calculated using a semiclassical time-dependent convergent close-coupling method. The helium target is treated using both frozen-core and multiconfiguration approximations. The electron-electron correlation of the target is fully accounted for in both cases. Double ionization and ionization with excitation channels are taken into account using an independent-event model. The Ne, Ar, Kr, and Xe atom wave functions are described in a model of six p-shell electrons above a frozen Hartree-Fock core with only one-electron excitations from the outer p shell allowed. Results obtained for helium in the multiconfiguration treatment are in better agreement with experimental measurements than other theories.